(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Preterm birth is one of the major conditions that affect on infant mortality and morbidity,many of maternal comorbidities effect on the fetus outcome, in this study we evaluate some of maternalcondition that effect on preterm birth and compare them with full term birth to know the most commonfactors associated with this condition to decrease the rate of preterm birth and reduce neonatal mortality andmorbidityMethods: A case control study was conducted at first of April to thirty of September 2018, in Al ZahraTeaching Hospital in Al Najaf City, 300 delivered pregnant women were participated divided to 100 casesas preterm delivery women and 200 controls as full term deliver women enrolled in the study, maternalcomorbidities were recorded and binary regression analysis was used for analysis of the study.Results: The study show many significant association between preterm birth and maternal risk factorsinclude, urinary tract infection (OR = 7.32), lower number of antenatal visit (OR=2.52), interval betweenpregnancy ?2 year (OR =1.973), premature rupture of membrane (or =6.55), oligohydramnios (OR =6.55),gestational diabetes (OR =3.45), abruptio placentae (OR = 5.06) and previous preterm labor (OR=3.68).Conclusion: Based on the results in the study the most determinants that affect on preterm birth were urinarytract infection, premature rupture of membrane and abruption placenta.